N-Gram Accuracy Analysis in the Method of Chatbot Response - Suryani Hormansyah, Dhebys; Larasati Amalia, Eka; Affandi, Luqman; Wahyu Wibowo, Dimas; Aulia, Indinabilah (International Journal of Engineering and Technology, 2018)
Chatbot is a computer program designed to simulate interactive conversations or communication to users. In this study, chatbot was created as a customer service that functions as a public health service in Malang. This application is expected to facilitate the public to find the desired information. The method for user input in this application used N-Gram. N-gram consists of unigram, bigram and trigram. Testing of this application is carried out on Â 3 N-gram methods, so that the results of the testsÂ have been done obtain the results for unigram 0.436, bigram 0.28, and trigram 0.26. From these results it can be seen that trigrams are faster in answering questions.